2011
DOI: 10.1042/bj4340571
|View full text |Cite
|
Sign up to set email alerts
|

Activation of hypoxia-inducible factor 1 in human T-cell leukaemia virus type 1-infected cell lines and primary adult T-cell leukaemia cells

Abstract: Following an investigation by the University of the Ryukyus, which revealed that figures that appeared within this paper had also been used in other papers without appropriate attribution or explanation (a pattern repeated over a number of publications in different journals), the Editorial Board of the Biochemical Journal retract this paper. The last author, Naoki Mori, takes full responsibility for the misrepresentation of data in this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Hypoxia plays a fundamental role in the pathophysiology of common causes of mortality, including stroke . Zinc release from a subset of glutamatergic terminals heightens under ischemia , leading to extracellular zinc increase from nanomolar to micromolar levels . During synaptic transmission, zinc can be released into the surrounding milieu making it available for entry into cells through gated zinc channels on neighboring cells .…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia plays a fundamental role in the pathophysiology of common causes of mortality, including stroke . Zinc release from a subset of glutamatergic terminals heightens under ischemia , leading to extracellular zinc increase from nanomolar to micromolar levels . During synaptic transmission, zinc can be released into the surrounding milieu making it available for entry into cells through gated zinc channels on neighboring cells .…”
Section: Discussionmentioning
confidence: 99%
“…The viral oncoproteins vGPCR (expressed by KSHV) and HBx (expressed by HBV) up‐regulate HIF‐1α expression by activating the MAPK pathway. HCV and HTLV‐1 have also been shown to increase HIF‐1α transcription, although the viral proteins involved have not yet been elucidated . HBV HBx stabilizes HIF‐1α in normoxia by inhibiting its interaction with pVHL , whereas KSHV LANA stimulates degradation of pVHL, thereby increasing the cellular pool of HIF‐1α .…”
Section: Angiogenesismentioning
confidence: 99%
“…Tax activation of Akt is also linked to NF-kappaB activation and p53 inhibition (76). Furthermore, activation of Akt by Tax prevents beta-catenin degradation and leads to its accumulation in the cell (81), and increases HIF-1alpha protein synthesis (82). Fukuda et al (75) reported high levels of phosphorylated Akt in ATLL cells and downregulated expression of inositol phosphatases PTEN and SH2-containing inositol phosphatase-1 (SHIP-1), which antagonize the PI3K-Akt pathway.…”
Section: Pi3k-aktmentioning
confidence: 99%